DISEMINASI PGPR SEBAGAI BIOAKTIVATOR DEKOMPOSISI BAHAN ORGANIK DI KELOMPOK USAHA TANI NAGARI SUNGAI ABANG KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Haliatur Rahma; Indra Dwipa; Agustian Agustian; Yaherwandi Yaherwandi; Reflinaldon Reflinaldon; Jumsu Trisno; Armansyah Armansyah; Gusmini Gusmini; Afrima Sari; Ryan Dwi Setyawan; Rika Hariance; Dede Suhendra (LPPM Universitas Andalas, 2023)
Nagari Sungai Abang is one of the areas in Lubuk Alung District, one of the rice production centers in Padang Pariaman Regency. One farming group that intensively cultivates rice is the Farming Business group. The problem with the farmer groups is their ignorance of the benefits of straw as a source of organic matter in the soil. The composting process is long, so farmers always burn rice straw after harvest in preparation for planting the following season. If the burning of straw is carried out continuously, it is feared that nutrients will be deficient in the soil. This activity aims to empower Farming Business groups in Nagari Sungai Abang, Lubuk Alung District, to utilize Plant Growth Promoting Rhizobacteria (PGPR) as a bio activator in making straw compost as organic fertilizer and an alternative to addressing the problem of straw waste in Nagari Sungai Abang, Lubuk Alung. This activity has been carried out in the Farming Group of Farmers in Sungai Abang Dalam Nagari Sungai Abang, Lubuk Alung District, Padang Pariaman Regency. The method used is outreach, counseling, and training to demonstrate making PGPR suspension and compost from straw. From the activities that have been carried out, ready-to-use PGPR is obtained as a bio activator reproduced in coconut water media and used as a bio activator to speed up the composting process. The conclusion of this activity is increasing farmers' understanding of the benefits of straw as a raw material for compost and the use of PGPR as a bioactivator in making straw compost.